Controlled crystallization of thermal evaporated GST-on-SOI for photonic neuromorphic application - Rakshitha Kallega; Roopali Shekhawat; K. Ramesh; Shankar Kumar Selvaraja (APL Materials)
Neuromorphic computing is inevitable in addressing the computing challenges faced by the current computing architecture. A nonvolatile process is one of the key elements in realizing a neuromorphic architecture. Realization of a photonic nonvolatile state has been a challenge. Germanium antimony telluride (GST) offers potential electrical and optical characteristics to realize an optical nonvolatile state through a material phase transition. In this work, we demonstrate controlled phase tuning of a thermally evaporated GST-integrated silicon ring-resonator for potential neuromorphic application. We present material characterization and device fabrication and correlate the electrical and photonic phase transitions of ring-integrated GST. The temperature cycling in temperature-dependent resistance measurement shows the feasibility of pinning the phase of the transition region, which could be exploited for multiple non-volatile states. Using a simple device architecture, we have exploited the non-volatile and gradual transition of thermally evaporated GST to access intermediate states, which can be realized as synaptic weights in neural networks.